2023
DOI: 10.3390/su151411025
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Rural Households’ Intensity of Flood Adaptation in the Fogera Rice Plain, Ethiopia: Evidence from Generalised Poisson Regression

Abstract: Effective adaptation to flooding risk depends on careful identification and combinations of strategies which, in turn, depends on knowledge of the determinants of flood adaptation. The main objective of this study was to examine the determinants of rural households’ intensity of flood adaptation in the Fogera rice plain, Ethiopia. A three-stage stratified sampling technique was employed to select 337 sample household heads. Primary data was collected through a structured household survey. Data analysis was acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…the least number of respondents reported a lack of attention, this is crucial in ood mitigation decisions. Lamond & Proverbs (2009) and Ndue et al (2023) reported that for ood resilience efforts to be successful, coordination and commitment from ood-prone populations are the best requirements. In this study, 4.5% of the households reported that their absence of commitment to ood mitigation was one of the constraining factors in the study area.…”
Section: Challenges Of Flood Mitigation Strategies In Study Areasmentioning
confidence: 99%
“…the least number of respondents reported a lack of attention, this is crucial in ood mitigation decisions. Lamond & Proverbs (2009) and Ndue et al (2023) reported that for ood resilience efforts to be successful, coordination and commitment from ood-prone populations are the best requirements. In this study, 4.5% of the households reported that their absence of commitment to ood mitigation was one of the constraining factors in the study area.…”
Section: Challenges Of Flood Mitigation Strategies In Study Areasmentioning
confidence: 99%
“…GP models can handle both over-dispersion and under-dispersion in the data and are more flexible in handling crash data with low sample mean compared to NB models [44]. The applications of GP models for analysing count data could be found in other fields; for instance, vehicle insurance claims [44], shipping damage incidents [45], environmental sciences [46], transport demand management [47] and medical sciences [48]. However, only a handful of studies have used the GP model for developing SPFs in transportation safety literature [21,26,49].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 20 years, the livelihoods of approximately 400 million people were annually affected by floods, resulting in 28,000 flood-related fatalities in Asia between 1987 and 1997 (United Nations University, WHO, 2001;National Disaster Management Authority NDMA, 2022). Studies documented that floods have widespread adverse effects globally (Alhassan, 2020;Ndue et al, 2023), exacerbating regional inequalities (Mohanty et al, 2020). Floods, a natural phenomenon, can have the most significant impact on the world's human population (Ahmadi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%